Efficient and convenient route for the synthesis of thiophene-2-carboxamidines as potential inhibitors of nitric oxide synthase (NOS) - Rashid, P. P.; Singh, Dharmendra; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2019)
A mild and efficient synthesis of substituted thiophene-2-carboxamidines which are potent inhibitors of nitric oxide synthase (NOS) is reported herein. The key step involves reaction of a BOC-protected imidazolyl thiophene-2-carboxamidine reactive intermediate with various primary amines to form BOC-thio-phene-2-carboxamidines which could be readily deprotected using TFA to furnish free carboxamidines. The method is very mild and tolerates diverse substituents including sensitive peptide and amino acid fragments. This new methodology represents a substantial improvement to the literature method owing to its simplicity and hassle-free purification procedures. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Amidines; Nitric oxide synthase (NOS); Nitric oxide synthase inhibitors; Thiophene-2-carboxamidines

Multi-purpose synthetic alpha-amino acid featuring coumarin and ureidopyrimidinone motifs on its backbone: Synthesis and peptide formation - Rashid, P. P.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2022)
Herein we report a synthetic a-amino acid featuring intensely fluorescent coumarin moiety and a strongly self-assembling ureidopyrimidinone (UPy) motif. This two-in-one synthetic amino acid, displaying both fluorescence and self-assembling property, has been synthesized in four easy steps starting from commercially available inexpensive starting materials. Suitably protected amino acid has been incorporated into various peptide sequences, following solution-phase peptide coupling protocols, to demonstrate its synthetic feasibility.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Fluorescent amino acids; Fluorescent Peptides; Quadruple hydrogen bonding; Unnatural amino acids; Ureidopyrimidinone